Strategies for improving resource assignment in test development projects in Company X using combined technology foresight techniques - Perez, Alex Penaflor II; Imbang, Glen (Quezon City University of the Philippines Diliman, 2012)
Company X primarily provides electronics manufacturing services (EMS) and power semiconductor assembly and test services to original equipment manufacturers in the automotive, industrial, medical, solar energy, telecommunications infrastructure, storage device, and consumer electronics industries worldwide. In addition, it offers test development and systems integration services; and distributes related products and equipment (from company profile). Over the years, Company X has realized that more and more OEM customers are looking for an EMS partner with test development capabilities. Having realized the need for this capability, Company X made a significant investment to acquire this capability in order for it to be more competitive in the EMS market. Test development department provides an internal service to the firm in the field of manufacturing test. It provides manufacturing test solutions as well as technical advises on how products are to be tested if a customer does not have the know-how. This group is the in-house expert in manufacturing test and manufacturing test methodologies. Simply put, this department simply knows test. The team is a pool of skilled and brilliant engineers from reputable universities in the Philippines who have gained a significant amount of industry experience in the field of test development and or test automation. The resource skills are obtained through formal training and development project exposure. Skillset is built over time therefore losing a resource will significantly set-back department operations, not to mention the investment the company has made in bringing up this capability. One of the issues that the resources commonly encounter is the overlapping schedule of projects assigned to them. Overlapping schedules results to an overstretching of the services a test developer can provide. Overstretching also means longer work hours in a desire to catch-up and immediately conclude the current project to gain more focus on the second one. This also includes extreme pressure to deliver and deploy developed test solutions to meet manufacturing commitment. In doing so, quality of work is sacrificed as well as striking an imbalance in the life of the resource. Based on this issue, it is attempted to use tools in foresight to gain added insight of the future of resource loading in the department. It is expected that having additional insight and information on how the future will be may make a significant difference in the decision making process of project loading. Framework of the project based on a series of foresight methods was crafted to serve as guide in undertaking the project. Foresight tools were carefully selected for suitability of applicability. Scanning provided an awareness of the factors affecting the project schedule and the shortening development timeline as well as the product development timeline. SWOT provided the department a realization of its strengths and weaknesses as well. Drawing from this realization, several initiatives can now be prepared to address the weaknesses and threats. Moreover, a plan on how to exploit the strength and opportunities can be made. Wild card provided that extra insight of unaccounted or unnatural factors affecting the conduct of the project and the project schedule itself. Trend analysis provided an insight that it will be effective if the project assigned to the resource should be a 5-month gap in-between automotive projects. Moreover, the trend also suggests that for the resource to be more effective, two (2) projects at the most can be assigned. The approach in using foresight tools to gain insight into the future to better plan resource loading in the department was achieved.
In partial fulfillment of the requirements in TM 299
Thesis
Keywords: Resource assignments; Combined technology foresight techniques; Test development projects